Shaping the 2010 Strategic Defence & Security Review : An Exercise in Squaring Conflicting Priorities - Jean-Claude Sergeant (Revue LISA)
This paper intends to explore the various determinants that intervene in the decision making process in the field of military equipment acquisition currently applied by the Ministry of Defence (MoD). Recent reports by the National Audit Office have highlighted the growing deficit incurred by the MoD regarding the cost of the fifteen most important arms projects at various stages of their completion cycle which have been vetted by the Defence Equipment and Support Unit of the MoD. The reports have estimated that the MoD was facing a shortfall between £6 and £36 billion over the next ten years (depending on the yearly growth of the MoD budget in real value). Part of this deficit originates in the programme delaying strategy resorted to by the MoD to ease financial pressure. But the main causes of this black hole are to be found in a combination of factors : the competition between the three Services for securing state-of-the-art equipment, often as a result of the required level of interoperability with American Forces ; the fact that this overspecification trend has been tacitly encouraged by the incapacity or unwillingness of the MoD to scrap an arms project once the main financial gate has been cleared irrespective of its wayward development ; the “cosy relationship” between major defence industrialists, MoD procurement officials and MPs, which often affects the way major contracts are awarded. Employment considerations are likely to trump cost saving attempts. Following the Strategic Defence and Security Review published in October 2010, British political leaders are now committed to reorganising the whole arms procurement system with a view to allowing British Forces access to the best possible capabilities at a cost affordable to the British taxpayer.